2023
DOI: 10.1038/s41598-023-28958-6
|View full text |Cite
|
Sign up to set email alerts
|

Biological mechanism of cell oxidative stress and death during short-term exposure to nano CuO

Abstract: It is well known that copper oxide nanoparticles (CuO NPs) are heavily toxic on in vitro systems. In human alveolar epithelial cells, the mechanism of toxicity is mostly related to oxidative insults, coming from intracellularly dissolved copper ions, finally leading to apoptotic or autophagic cell death. Our hypothesis is based on possible early oxidative events coming from specific NP surface reactivity able to undermine the cell integrity and to drive cell to death, independently from Lysosomal-Enhanced Troj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 56 publications
4
5
0
Order By: Relevance
“…This is in line with the other findings that report a toxicity mechanism mainly based on oxidative insults [43]. Similar results were also observed in the A549 cell line, revealing an acute genotoxicity of nano-sized CuO, which is well captured by our framework [43][44][45].…”
Section: Network-based Approach Can Be Used To Mechanistically Interp...supporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with the other findings that report a toxicity mechanism mainly based on oxidative insults [43]. Similar results were also observed in the A549 cell line, revealing an acute genotoxicity of nano-sized CuO, which is well captured by our framework [43][44][45].…”
Section: Network-based Approach Can Be Used To Mechanistically Interp...supporting
confidence: 93%
“…Interestingly, the predicted MIEs included alteration of the oxidative status in all the test systems, and alteration of ion pumps and receptors in both lung and BEAS-2B. This is in line with the other findings that report a toxicity mechanism mainly based on oxidative insults [43]. Similar results were also observed in the A549 cell line, revealing an acute genotoxicity of nano-sized CuO, which is well captured by our framework [43][44][45].…”
Section: Network-based Approach Can Be Used To Mechanistically Interp...supporting
confidence: 90%
“…Recent studies have demonstrated that testes are susceptible to oxidative stress because of exposure to copper oxide nanoparticles. Reactive oxygen species (ROS) generation and the body's capacity to detoxify them are out of balance, which causes oxidative stress and cellular damage (Moschini et al, 2023).Even though metal ion dissolution may ultimately contribute to the cytotoxicity caused by CuO NPs, most research tends to blame the harmful impact on the particle's reactivity. Numerous articles have noted that less than half of the overall impact of CuO NPs cytotoxicity is attributable to the extracellularly dispersed copper ions confirming that oxidative stress is a significant factor in cell death (Hanagata et al, 2011;(Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Physisorption of gases, with special reference to the evaluation of surface area and pore size distribution (IUPAC Technical Report). Pure and Applied Chemistry, 87 (9)(10)…”
mentioning
confidence: 99%
“…Cu 2 O and CuO NPs would release ions in the endosomal compartment as they were soluble in the culture medium. [82,83] In the following trafficking, NMs in the endosome were released into the extracellular environment through endosome recycling, or accumulated in multivesicular endosomes followed by transport to lysosomes. [30,84] The latter trafficking is always along with progressive acidification and degradation.…”
Section: The Intracellular Trafficking Of Nmsmentioning
confidence: 99%